Diversity of orthoptera (grasshoppers and crickets) at paddy field in Sri Menanti, Kuala Pilah, Negeri Sembilan / Narisa Abdul Rahman - Abdul Rahman, Narisa (2016)
A study on diversity of Orthoptera at paddy field site in Sri Menanti, Kuala Pilah, Negeri Sembilan aimed to record the species composition and the diversity of Orthoptera at the particular area. The trapping method used are sweeping nets, yellow pan traps, light traps, and direct collection. As a result, four families were found on that area which are Acrididae, Gryllidae, Pyrgomorphidae, and Tettigoniidae. There are 101 number of individuals obtained during sampling period, and five genus are found at the area. The genus are Syrbula, Atractomorpha, Melanoplus, Acheta, and Tettigonia. The largest group of genus found is Syrbula with a total of 40, followed by Atractomorpha with 23, Melanoplus and Acheta both with 16, and the least group of genus is Tettigonia with a total of only six. There are three statistical analysis used in this study which are Shannon-Wiener Diversity, Margalef Richness, and Shannon Evenness. The value of Shannon-Wiener Diversity (H+) is 1.46, while for Margalef Richness (R) is 0.87. The value of Shannon Evenness (E) is 0.9.